The Drazin inverses of infinite triangular matrices and their linear preservers - Słowik, R. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We consider the ring of all infinite (N × N) upper triangular matrices over a field F. We give a description of elements that are Drazin invertible in this ring. In the case where F is such that char(F) ot = 2 and | F| > 4, we find the form of linear preservers for the Drazin inverses.